Liquid Chromatographic Method For Simultaneous Estimation Of Atorvastatin Calcium And Amlodipine Besylate In Pharmaceutical Dosage Forms - SASMITA KU. ACHARJYA; M.MATHRUSRI ANNAPURNA; SAILAJA KOYA (International Journal of Pharma and Bio Sciences, 2010)
An isocratic RP-HPLC method was developed and validated for the quantitation of Atorvastatin calcium and Amlodipine besylate in combined tablet dosage forms. Quantitation was achieved using a reversed-phase Hypersil silica BDS (250x4.6mm with 5µ particle size) column at ambient temperature with mobile phase consisting of 0.05M ammonium acetate buffer (pH-4) and acetonitrile in the ratio (40 + 60, v/v). The flow rate was 1.0 mL/min. Measurements were made at a wavelength of 240.0nm. The proposed method was validated for selectivity, precision, linearity and accuracy. The assay method was found to be linear from 30.0-70.0 µg/mL for Amlodipine besylate and 60.0-140.0 µg/mL for Atorvastatin calcium. All validation parameters were within the acceptable range. The developed method was successfully applied to estimate the amount of Atorvastatin calcium and Amlodipine besylate in combined dosage forms.